Lower Pannonia before and after the Treaty of Aachen - Gračanin, Hrvoje (2012)
The proposed paper endavours to survey and analyze the main historical processes in Lower Pannonia between the rivers Sava, Drava and Danube during the first decades of the 9th century. The focus will be on the circumstances that led to creation of new political realities in the Middle Danube area in the late 8th and the early 9th centuries, on the establishment of a new polity between the rivers Sava, Drava and Danube under Frankish tutelage as to serve their overall strategic interests, and on the clash between the recently formed Slavic elite under the Lower Pannonian dux Liudevit and his Frankish overlords. The special attention will be given to the question whether the Frankish-Byzantine relations influenced the Frankish military-political solutions for the area between the Sava, Drava and Danube, and to what extent the dux Liudevit's conspiring with, as it turned out, the pro-Byzantine patriarch Fortunatus of Grado may have been construed by the Frankish authorities as a potential threat to their overall position in the Adriatic-Danubian region. It will be contended that the Frankish thrust into the Middle Danube area may have served several major purposes. In addition to securing the eastern frontier of the Frankish realm, this expansionist move against the Avar Khaganate was likely aimed at strengthening the Frankish position in the wider region given the deteriorating relations with the Byzantines ; furthermore, should Charlemagne and his advisors be allowed to have enjoyed a well-informed insight into the situation in the Southeast Europe, the attack against the Avars may also be seen as a sort of a pre-emptive step to forestall any similar possible action either by the Byzantines or by the Bulgars at any point in the future ; moreover, it brought a large portion of the territory that had once belonged to the Roman Empire under the Frankish sway thus giving more substance to Charlemagne's claim at the renovatio Imperii Romani ; and finally, it gave the Franks the opportunity to deepen and intensify their policy towards the regional Slavic groups, which was the more important since the good relations with the Slavs proved of some value in repeated attempts by the Franks to pacify the Saxons, and the Franks might have expected the same support from the Middle Danubian and Adriatic Slavs against the Byzantium. The provisions of the Treaty of Aachen presumably also affected the region between the rivers Sava, Drava, and Danube which, by that time, had been verly likely already organized in the Principality of Lower Pannonia, although the sources are silent on this. It may even be that the Frankish authority in this region was now if not officialy, but at least tacitly recognized by the Byzantines. However, it would seem that the rebellion of the dux Liudevit provided them on surface with a chance to challenge the Frankish dominance. The course and details of the rebellion warrant re-examination in this context, especially in light of the fact that Constantine Porphyrogenitus attributed to the Byzantine Emperor Michael II (820-829), a contemporary of the rebellion, the responsibility for the total collapse of the Byzantine influence on the East Adriatic coast and in Slavic lands of the western Balkans.
Projekt MZOS
Projekt MZOS
ENG